Cenas da vida virtual: amor, corpo e subjetividade numa sociedade do consumo e do entretenimento - Garcia, Margarete Schimidt de Mendes (2009)
Humanity is, in its own course, increasingly turning itself to a life on the computer’s screen. Self relations, relations with the body, with the other, with consume, with culture, with life, can be experimented in a cyberspace piece of territory called metaverse. This place supports not only a representation of life, but also its creation through graphic interfaces, images of a virtual existence, whose expression has stained the bourderline between the so called real and virtual, making the convivence and the bridge between these two worlds subtle and, sometimes, problematic. The entertainment, through technology, may assume the living place of an intimity that implies the totality of a being. Work, social relations, the exercice of the passions and sexuality can be experienced in a very profound and vivid way in this sinthetic world. The entry and the research inside the tridimensional interactive online virtual world of Second Life has shown that our presence in this piece os cyberspace may signify a kind of fold, which puts in contact unknown surfaces. It may also question and tensionate interactions and values based in a social body and code of a mechanich-analogic world.